INDONESIAN MUSLIM WOMEN AND THE GENDER EQUALITY MOVEMENT - Alimatul Qibtiyah (Journal of Indonesian Islam, 2009)
Throughout the history of Indonesia, the concepts of gender and power-relations between men and women have been linked to a shifting and fluctuating idea of what constitutes good women, good men, and good gender relationships within the context of Indonesia and Islam. To analyse these changing attitudes to women’s issues in Indonesia, we need to pay attention to several points: the character of the women’s organizations, whether fully independent, semi autonomous, or subsidiaries of existing male organizations; the important issues rising within the movements, as well as the strategies to deal with them; and lastly the influential factor of government intervention in the women’s movement. This paper tries to explore the Muslim women’s movement and its strategy to accommodate or resist from the domination of Islam in terms of the nation state, the constitution and the dominant cultural norms in Indonesia.